Calcification of the elastic component: the impact on the cardiovascular system - Francesco Demetrio Lofaro; Alessia Mazzilli; Susanna Bonacorsi; Daniela Quaglino; Federica Boraldi (Frontiers in Cardiovascular Medicine)
In the cardiovascular system, elastic fibres exert a fundamental role providing the long-range elasticity required for physiological functions. Elastic fibres are complex in composition and structure containing, in addition to elastin, a wide range of matrix components, such as microfibrillar proteins, calcium-binding proteins and glycosaminoglycans. Changes in composition and/or structure can affect the biomechanics of the tissue as well as the intrinsic affinity of elastin for Ca2+ ions. Mineralization of elastic fibres can occur in genetic as well as in age-related chronic diseases. In cardiovascular diseases, for instance, calcification represents an integral part of the pathogenetic process, although the regulatory mechanisms are not completely understood. Therefore, a focus is given on elastin synthesis and assembly, on elastic fibre components and on elastin degradation. Moreover, the role and the impact of altered composition and supramolecular organization of elastic fibres are described in the context of the calcified cardiovascular system. Finally, some in vitro and in vivo models of elastic fibres calcification are presented and discussed.